1995
DOI: 10.1128/jvi.69.6.3308-3314.1995
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of N-terminal amino acid residues of gp41 for human immunodeficiency virus type 1-mediated cell fusion

Abstract: An expression vector was designed to test the structural requirements of the gp41 N terminus for human immunodeficiency virus type 1-induced membrane fusion. Mutations in the region coding for the N terminus of gp41 were found to disrupt glycoprotein expression because of deleterious effects on the Rev-responsive element (RRE). Insertion of an additional RRE in the 3-noncoding sequence of env made possible efficient glycoprotein expression, irrespective of the mutations introduced into the RRE in the natural l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 61 publications
2
64
0
Order By: Relevance
“…FP sequence is absolutely required for gp41 fusogenic activity [10][11][12]. Previous studies have demonstrated that viral FP-induced pore-formation in liposomes is sensitive to physiologically relevant factors such as single blocking mutations [33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…FP sequence is absolutely required for gp41 fusogenic activity [10][11][12]. Previous studies have demonstrated that viral FP-induced pore-formation in liposomes is sensitive to physiologically relevant factors such as single blocking mutations [33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…The fusion peptide (FP) was located at the N-terminus of syncytin TM subunit and consisted of hydrophobic, glycine-rich residues, which was essential for the initial penetration of the target cell membrane in many enveloped viruses, e.g., HIV-1 [23,24]. The hydrophobic 4-3 heptad repeat (HR) regions located adjacently to the N-and C-terminal portions of syncytin TM subunit were named as NHR and CHR, respectively ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely to be the case for the fusion peptide of gp41. Since the three residues N-terminal to the first residue of the helix are crucial to the stability of the helix, the experiments of successive deletion of residues N-terminal to F8 reported by Schaal et al (1995) can be rationalized. Thus, the capacity of gp41 to induce syncytium was greatly reduced as F8 became the fourth residue from the N-terminus of transmembrane glycoprotein as a result of deletion ; a complete interruption of syncytium formation was observed as further deletion rendered F8 the third or the second residue from the Nterminus of transmembrane glycoprotein.…”
Section: Discussionmentioning
confidence: 99%